2014
DOI: 10.1080/19425120.2014.893467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coastal Urbanization on Salt‐Marsh Faunal Assemblages in the Northern Gulf of Mexico

Abstract: Coastal landscapes in the northern Gulf of Mexico, specifically the Mississippi coast, have undergone rapid urbanization that may impact the suitability of salt‐marsh ecosystems for maintaining and regulating estuarine faunal communities. We used a landscape ecology approach to quantify the composition and configuration of salt‐marsh habitats and developed surfaces at multiple spatial scales surrounding three small, first‐order salt‐marsh tidal creeks arrayed along a gradient of urbanization in two river‐domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 95 publications
1
20
0
Order By: Relevance
“…Studies in many locations have found that armouring influenced localized fish abundances or the composition of fish communities Peterson et al 2000;Davis, Takacs & Schnabel 2006;Toft et al 2007;Pastor et al 2013;Lowe & Peterson 2014). Some of these studies also found that armoured shorelines supported lower fish community integrity measured by indices such as diversity and richness (Bilkovic & Roggero 2008;Strayer et al 2012;Balouskus & Targett 2016;Torre & Targett 2016), and lower annual stability of fish abundance and community composition .…”
Section: Documented Effects Of Shoreline Armouring On Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in many locations have found that armouring influenced localized fish abundances or the composition of fish communities Peterson et al 2000;Davis, Takacs & Schnabel 2006;Toft et al 2007;Pastor et al 2013;Lowe & Peterson 2014). Some of these studies also found that armoured shorelines supported lower fish community integrity measured by indices such as diversity and richness (Bilkovic & Roggero 2008;Strayer et al 2012;Balouskus & Targett 2016;Torre & Targett 2016), and lower annual stability of fish abundance and community composition .…”
Section: Documented Effects Of Shoreline Armouring On Fishmentioning
confidence: 99%
“…; Pastor et al . ; Lowe & Peterson ). Some of these studies also found that armoured shorelines supported lower fish community integrity measured by indices such as diversity and richness (Bilkovic & Roggero ; Strayer et al .…”
Section: Documented Effects Of Shoreline Armouring On Fishmentioning
confidence: 99%
“…For example, temporally variable sturgeon movement downriver during fall emigration occurred in drought years in the Pascagoula River compared with fish pulsing quickly from the summer holding area in wet years (Heise et al 2005). This influence of natural variability coupled with the increased urbanization in the coastal zone worldwide (Flowers et al 2009;Peterson and Lowe 2009;Lowe and Peterson 2014) and issues with water withdrawals and climate change (USFWS and Gulf States Marine Fisheries Commission 1995;Flowers et al 2009;USFWS 2009;Mims and Olden 2012;Farrae et al 2014) make it vital that we understand long-term ontogenetic habitat use patterns and how natural riverine variability might influence the initiation of migration of anadromous species. This information will help ensure that we are knowledgeable when promoting any future recovery actions.…”
mentioning
confidence: 99%
“…Density of estuary-resident and estuary-dependent species (hereafter grouped together as estuarine) can reflect habitat quality (Szedlmayer and Able 1996;Rountree and Able 2007). As estuaries continue to be modified and degraded, additional processes such as competitive release and water quality tolerance (Lowe and Peterson 2014) can also contribute to species presence and density.…”
Section: Discussionmentioning
confidence: 99%